2014
DOI: 10.3897/zookeys.449.7494
|View full text |Cite
|
Sign up to set email alerts
|

Amphibians of Serra Bonita, southern Bahia: a new hotpoint within Brazil’s Atlantic Forest hotspot

Abstract: We studied the amphibian community of the Private Reserve of Natural Heritage (RPPN) Serra Bonita, an area of 20 km2 with steep altitudinal gradients (200–950 m a.s.l.) located in the municipalities of Camacan and Pau-Brasil, southern Bahia State, Brazil. Data were obtained at 38 sampling sites (including ponds and transects within the forest and in streams), through active and visual and acoustic searches, pitfall traps, and opportunistic encounters. We recorded 80 amphibian species distributed in 15 families… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 62 publications
(70 reference statements)
4
30
0
1
Order By: Relevance
“…Fourteen of the 69 recorded species ( Frostius erythrophthalmus , “ Eleutherodactylus bilineatus , Adelophryne cf. pachydactyla, A. mucronatus , Gastrotheca recava , Hylomantis aspera , Bokermannohyla capra , Phasmahyla timbo , Phyllodytes praeceptor , Phyllodytes wuchereri , Ololygon strigilata , Physalaemus camacan , Chiasmocleis cordeiroi and C. crucis ) are also endemic to Bahia (Angulo 2008a, Juncá and Pimenta 2004, Peixoto and Pimenta 2004, Borges-Najosa and Juncá 2004, Lourenço-de-Moraes et al 2012, Teixeira Jr. et al 2012, Silvano and Pimenta 2010, Napoli and Pimenta 2009, Angulo 2009, Rodrigues 2006, Juncá and Silvano 2004, Angulo 2008b, Forlani et al 2013). The results of our study expand the known distribution of Adelophryne mucronatus 60 km to the north (Lourenço-de-Moraes et al 2012, Dias et al 2014a). Two species were recorded by collecting only a single individual per species: Aparasphenodon brunoi , a bromeliad species, which had its distribution recently increased from the municipality of Una to the REM (Ruas et al 2013), and Dermatonotus muelleri , which is a species typically found in open areas..…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Fourteen of the 69 recorded species ( Frostius erythrophthalmus , “ Eleutherodactylus bilineatus , Adelophryne cf. pachydactyla, A. mucronatus , Gastrotheca recava , Hylomantis aspera , Bokermannohyla capra , Phasmahyla timbo , Phyllodytes praeceptor , Phyllodytes wuchereri , Ololygon strigilata , Physalaemus camacan , Chiasmocleis cordeiroi and C. crucis ) are also endemic to Bahia (Angulo 2008a, Juncá and Pimenta 2004, Peixoto and Pimenta 2004, Borges-Najosa and Juncá 2004, Lourenço-de-Moraes et al 2012, Teixeira Jr. et al 2012, Silvano and Pimenta 2010, Napoli and Pimenta 2009, Angulo 2009, Rodrigues 2006, Juncá and Silvano 2004, Angulo 2008b, Forlani et al 2013). The results of our study expand the known distribution of Adelophryne mucronatus 60 km to the north (Lourenço-de-Moraes et al 2012, Dias et al 2014a). Two species were recorded by collecting only a single individual per species: Aparasphenodon brunoi , a bromeliad species, which had its distribution recently increased from the municipality of Una to the REM (Ruas et al 2013), and Dermatonotus muelleri , which is a species typically found in open areas..…”
Section: Discussionsupporting
confidence: 86%
“…The increasing number of publications reporting the geographic distribution of several species (e.g., Camurugi et al 2010, Dias et al 2011, Mattedi and Pontes 2014, Dias et al 2014a) and the description of new species corroborate this data (e.g., Napoli et al 2011, Lourenço-de-Moraes et al 2012, Teixeira-Jr et al 2013, Caramaschi et al 2013, Pontes et al 2014, Juncá et al 2015, Dias et al 2017, Marciano et al 2017, Vörös et al 2017). Inventories increase our knowledge of amphibian community composition and allow a better understanding of species diversity patterns (Haddad 1998).…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…(Juncá, 2006), and RPPN Serra Bonita (n = 80 spp.) (Dias et al, 2014), all in the state of Bahia, have a higher amphibian diversity.…”
Section: Amphibiansmentioning
confidence: 98%
“…), with 59% of the species that occur in the State (see Santos & Carnaval, 2002;Moura et al, 2011). The Serra do Urubu mountain range has one of the richest amphibian faunas of the Brazilian Atlantic Forest (see Dias et al, 2014 for a review), and is the fourth richest area in the northeastern Atlantic Forest, only the Reserva Ecológica Michelin (n = 48 spp.) (Camurugi et al, 2010), Serra da Jibóia and Serra do Timbó (n = 53 spp.)…”
Section: Amphibiansmentioning
confidence: 99%